PENGARUH E-COMMERCE, INFLASI, DAN NILAI TUKAR TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Lastri, Widya Ayu; Anis, Ali (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This Study aims to examine and to analisys the influencing factors on economic growth in Indonesia, which the variables are e-commerce, inflation and exchange rate. This study is associative descriptive research, which using secondary data from 2011Q1-2018Q4 that obtained from relevant institutions and agencies. Analisys using Error Correction Model (ECM) method. This study using Ordinary Lest Square (OLS) method to know the long term effect and ECM to know the short term effect at one blow.The study found that in the long term, e-commerce and exchange rate have a significant effect and inflation have not a significant effect. And in the short term, e-commerce have a positive and significant effect, while inflation and exchange rate have a negative and not significant.